PENGARUH KARAKTER RISIKO EKSEKUTIF TERHADAP TAX AVOIDANCE DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERATING - Wendaka Setiya Pratama; Eny Suprapti; Ahmad Syaiful Hidayat (Jurnal Akademi Akuntansi, 2019)
The purpose of this study was to determine the effect of Executive Characteristics on Tax Avoidance with Independent Commissioners as moderating variables. This research is associative research. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2017. The number of samples from this study were 94 companies. Sampling was done using purposive sampling method. The method of analysis carried out in this study was the test of moderated regression analysis (MRA), classical assumption test, and partial test (t test). The results showed that the executive character had a significant effect on tax avoidance. Partially, the executive character has a significant positive effect on tax avoidance, and the independent commissioner moderates the relationship between the executive character and tax avoidance.